(untitled) (SAARC Journal of Agriculture, 2026)
Despite their nutritional importance, jackfruit seeds are rarely used in food preparations due to their recalcitrant nature and limited availability after the seasonal glut. The study aimed to create nutritious bread enriched with the jackfruit seed flour in place of wheat flour. The nutritional, physical and sensorial properties of bread using various proportions (0, 5, 10 and 15%) of jackfruit seed flour were examined. The results of proximate analysis revealed that adding 15% jackfruit seed flour to breads significantly (P<0.05) increased the content of protein, moisture, ash and dietary fiber (12.90±0.05% to 13.83±0.12%, 26.90±0.12% to 28.63±0.16%, 0.68±0.20% to 1.07±0.8% and 1.77±0.10% to 2.07±0.15%, respectively), while decreasing fat (3.60±0.06% to 1.97±0.07%) content. It was observed that formulated breads were more nutritious than the control sample. In comparison to the control and other samples, bread made with a 10% jackfruit seed flour substitute was found more palatable, based on the physical appearance and sensory attributes. As a result, jackfruit seed may be considered as an unexplored source of dietary supplements and a possible source of natural, active chemicals for use in food applications. SAARC J. Agric., 23(2): 203-215 (2025)